Efficacy of Yoga vs Cognitive Behavioral Therapy vs Stress Education for the Treatment of Generalized Anxiety Disorder: A Randomized Clinical Trial - Simon, Naomi M. (JAMA Psychiatry, 2021)
IMPORTANCE: Generalized anxiety disorder (GAD) is common, impairing, and undertreated. Although many patients with GAD seek complementary and alternative interventions, including yoga, data supporting yoga’s efficacy or how it compares to first-line treatments are lacking. OBJECTIVES: To assess whether yoga (Kundalini yoga) and cognitive behavioral therapy (CBT) for GAD are each more effective than a control condition (stress education) and whether yoga is noninferior to CBT for the treatment of GAD. DESIGN, SETTING, AND PARTICIPANTS: For this randomized, 3-arm, controlled, single-blind (masked independent raters) clinical trial, participants were recruited from 2 specialty academic centers starting December 1, 2013, with assessment ending October 25, 2019. Primary analyses, completed by February 12, 2020, included superiority testing of Kundalini yoga and CBT vs stress education and noninferiority testing of Kundalini yoga vs CBT. INTERVENTIONS: Participants were randomized to Kundalini yoga (n = 93), CBT for GAD (n = 90), or stress education (n = 43), which were each delivered to groups of 4 to 6 participants by 2 instructors during twelve 120-minute sessions with 20 minutes of daily homework. MAIN OUTCOMES AND MEASURES: The primary intention-to-treat outcome was acute GAD response (Clinical Global Impression–Improvement Scale score of much or very much improved) after 12 weeks as assessed by trained independent raters. RESULTS: Of 538 participants who provided consent and were evaluated, 226 (mean [SD] age, 33.4 [13.5] years; 158 [69.9%] female) with a primary diagnosis of GAD were included in the trial. A total of 155 participants (68.6%) completed the posttreatment assessment. Completion rates did not differ (Kundalini yoga, 60 [64.5%]; CBT, 67 [74.4%]; and stress education, 28 [65.1%]: χ(2) = 2.39, df = 2, P = .30). Response rates were higher in the Kundalini yoga group (54.2%) than in the stress education group (33.%) (odds ratio [OR], 2.46 [95% CI, 1.12-5.42]; P = .03; number needed to treat, 4.59 [95% CI, 2.52-46.19]) and in the CBT group (70.8%) compared with the stress education group (33.0%) (OR, 5.00 [95% CI, 2.12-11.82]; P < .001; number needed to treat, 2.62 [95% CI, 1.91-5.68]). However, the noninferiority test did not find Kundalini yoga to be as effective as CBT (difference, 16.6%; P = .42 for noninferiority). CONCLUSIONS AND RELEVANCE: In this trial, Kundalini yoga was efficacious for GAD, but the results support CBT remaining first-line treatment. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01912287